Problems and solutions of studying the history of Russian literature - Umarbekova Gulnora Anvarbekovna (Genius Publishing Group, 2023)
This article delves into the challenges and solutions in the study of Russian literary history. It examines the complexities of this literary tradition, analyzes various research methods, and offers insights into understanding the Russian literary canon. By addressing these issues, we aim to foster a deeper appreciation and comprehension of Russian literature.
Keywords: Russian literature; historical analysis; challenges; solutions